Antepartum Risk Factors for Peripartum Hysterectomy in Women with Placenta Previa - Sündüz Özlem Altınkaya; Sümeyra Nergiz; Metin Güldaş; Selda Demircan Sezer; Hasan Yüksel (Medical Network, 2016)
OBJECTIVE: The aim of the present study was to identify the antepartum risk factors for peripartum hysterectomy in women with placenta previa. STUDY DESIGN: The medical records of 57 women, who underwent cesarean because of placenta previa during the period January 2006-January 2013, were reviewed retrospectively. Antepartum characteristics of women who did and did not undergo peripartum hysterectomy were compared. RESULTS: Among the 57 cases with placenta previa, peripartum hysterectomy was required in 6 (10.5%) women. A statistically increased risk emerged for a history of repeated cesarean delivery (p=0.045), placental adhesive disorders (p<0.001), and an estimated blood loss ≥2000 ml (p<0.001). CONCLUSION: The present study confirmed placenta previa is a condition for a substantial risk of peripartum emergent hysterectomy. An increasing number that of previous cesareans, placental adhesive disorders and blood loss ≥2000 ml were found to be associated with the risk. Antepartum evaluation of adhesive disorders with imaging studies may play a crucial role in predicting hysterectomy in these cases.